Effects of commercial enzymes in diets containing dried distillers grains with solubles for nursery pigs - Jones, C.K.; Bergstrom, J.R.; Tokach, Michael D.; DeRouchey, Joel M.; Nelssen, Jim L.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
Two experiments utilizing a total of 530 pigs were conducted to evaluate the effects of commercial enzymes in diets containing dried distillers grains with solubles (DDGS) on nursery pig growth performance. In Exp. 1, 180 pigs (initially 19.9 lb) were used in a 27-d growth trial to compare the effects of Easyzyme, Hemicell-W, and Porzyme in diets containing 30% DDGS on weanling pig performance. The 5 dietary treatments fed were a positive control (corn-soybean meal-based diet), negative control (diet with 30% corn DDGS), and the negative control diet with either 0.05% Easyzyme, 0.05% Hemicell-W, or 0.05% Porzyme added. Overall (d 0 to 27), pigs fed the diet containing Easyzyme had lower (P < 0.05) ADG than pigs fed the positive control diet. Pigs fed diets containing Hemicell-W had lower (P < 0.05) ADG than pigs fed the control diet with or without 30% DDGS or the diet containing Porzyme. Pigs fed the diet containing Porzyme had ADG similar (P > 0.10) to that of pigs fed the control diets with or without 30% DDGS. There were no differences (P > 0.10) in ADFI or F/G.In Exp. 2, 350 pigs (initially 24.3 lb) were used to evaluate the effects of a commercial enzyme in diets containing a variety of levels and sources of DDGS on nursery pig performance. The 10 experimental treatments were (1) corn-soybean meal positive control, (2) 15% corn DDGS, (3) 30% corn DDGS, (4) 30% corn DDGS + 0.05% Easyzyme, (5) 15% milo DDGS from source 1, (6) 30% milo DDGS from source 1, (7) 30% milo DDGS from source 1 + 0.05% Easyzyme, (8) 15% milo DDGS from source 2, (9) 30% milo DDGS from source 2, and (10) 30% milo DDGS from source 2 + 0.05% Easyzyme. Overall (d 0 to 21), there was no (P > 0.10) enzyme × DDGS source interaction for any of the measured growth variables. Pigs fed diets with increasing corn DDGS had ADG, ADFI, and F/G similar (P > 0.10) to those of pigs fed the control diet. Pigs fed diets with increasing milo DDGS had poorer (linear, P = 0.002) F/G than pigs fed the control diet. Also, pigs fed diets containing milo DDGS had poorer (P = 0.04) F/G than pigs fed diets containing corn DDGS. However, pigs fed different sources of milo DDGS had similar (P > 0.10) ADG, ADFI, and F/G. Adding 0.05% Easyzyme to the diets containing 30% DDGS did not influence (P > 0.10) ADG, ADFI, or F/G. In summary, feeding diets with milo DDGS resulted in poorer F/G with no change in ADG compared with feeding the control diet or diets containing corn DDGS. Adding enzymes to corn-soybean meal-based diets containing high levels of DDGS did not improve any of the growth performance variables.
Keywords: Distillers; Enzyme; Growth; Nursery pig